Muscle Development of Livestock Animals: Physiology, Genetics and Meat Quality 2004
DOI: 10.1079/9780851998114.0363
|View full text |Cite
|
Sign up to set email alerts
|

Post-mortem muscle proteolysis and meat tenderness.

Abstract: Connective tissue provides the support at a number of levels via the endomysium, perimysium or epimysium and maintains the integrity of the contractile apparatus made up of myofibrillar proteins such as actin and myosin and important associated proteins such as titin and nebulin. Proteins such as desmin, talin and α-actinin also help to maintain the framework within which the contractile proteins function. Degradation of proteins such as titin, nebulin and desmin will lead to myofibril disruption and contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…The degradation of desmin is thought to significantly contribute to tenderisation (Hopkins and Taylor, 2004;Geesink et al, 2006). Research by Koohmaraie et al (1995) found that in lambs carrying the callipyge phenotype, which is associated with increased levels of calpastatin and increased meat toughness, there was a reduction in the degradation of a number of myofibrillar proteins including desmin in comparison to normal lambs, suggesting its importance with regard to meat tenderness.…”
Section: Effect Of Incubation Time On Myofibril Protein Degradationmentioning
confidence: 99%
“…The degradation of desmin is thought to significantly contribute to tenderisation (Hopkins and Taylor, 2004;Geesink et al, 2006). Research by Koohmaraie et al (1995) found that in lambs carrying the callipyge phenotype, which is associated with increased levels of calpastatin and increased meat toughness, there was a reduction in the degradation of a number of myofibrillar proteins including desmin in comparison to normal lambs, suggesting its importance with regard to meat tenderness.…”
Section: Effect Of Incubation Time On Myofibril Protein Degradationmentioning
confidence: 99%
“…In addition to cold shortening reduction (Chrystall and Devine 1985;Devine et al 2004), the benefits of ES on meat tenderness may be due to aging acceleration caused by faster ATP depletion, hastening rigor onset and allowing for tenderization to begin sooner and at higher temperature (Hwang et al 2003;Simmons et al 2008). It is well recognized that myofibrillar and cytoskeletal proteolysis occurs during aging and enhances meat tenderness (Koohmaraie 1994;Taylor et al 1995;Hopkins and Taylor 2004), even if mechanisms are still under investigation. The calpain/ calpastatin system plays a major role in the process (Dransfield 1993;Koohmaraie 1994;Koohmaraie and Geesink 2006), but other proteases (Ouali et al 2006;Kemp and Parr 2012) or mechanisms (Wu and Smith 1987;Takahashi 1996) could be implicated.…”
mentioning
confidence: 94%
“…Postmortem conversion of muscle to meat involves several biochemical modifications and processes that begin with a metabolic shift from an aerobic to an anaerobic state. This is followed by production of lactic acid which decreases pH of the muscle; activation of different proteinase systems which degrade muscle proteins and activity of other enzymatic mechanisms which effect and/or produce specific metabolites (Hopkins & Taylor 2003). Low growth rate pigs exhibited a fatter carcass, associated with markedly higher activity of enzymes involved in lipogenesis, such as fatty acid synthase and malic enzyme (Bee 2007).…”
Section: Introductionmentioning
confidence: 99%